Does creatine supplementation improve the plasma lipid profile in healthy male subjects undergoing aerobic training? - Scagliusi Fernanda B; Benatti Fabiana B; Artioli Guilherme G; Ugrinowitsch Carlos; Gualano Bruno; Harris Roger C; Lancha Antonio H (Taylor & Francis Group, 2008)
Abstract We aimed to investigate the effects of creatine (Cr) supplementation on the plasma lipid profile in sedentary male subjects undergoing aerobic training. Methods Subjects (n = 22) were randomly divided into two groups and were allocated to receive treatment with either creatine monohydrate (CR) (~20 g·day-1 for one week followed by ~10 g·day-1 for a further eleven weeks) or placebo (PL) (dextrose) in a double blind fashion. All subjects undertook moderate intensity aerobic training during three 40-minute sessions per week, over 3 months. High-density lipoprotein cholesterol (HDL), low-density lipoprotein cholesterol (LDL), very low-density lipoprotein cholesterol (VLDL), total cholesterol (TC), triglyceride (TAG), fasting insulin and fasting glycemia were analyzed in plasma. Thereafter, the homeostasis model assessment (HOMA) was calculated. Tests were performed at baseline (Pre) and after four (Post 4), eight (Post 8) and twelve (Post 12) weeks. Results We observed main time effects in both groups for HDL (Post 4 versus Post 8; P = 0.01), TAG and VLDL (Pre versus Post 4 and Post 8; P = 0.02 and P = 0.01, respectively). However, no between group differences were noted in HDL, LDL, CT, VLDL and TAG. Additionally, fasting insulin, fasting glycemia and HOMA did not change significantly. Conclusion These findings suggest that Cr supplementation does not exert any additional effect on the improvement in the plasma lipid profile than aerobic training alone.